Publicar teatro como prática cênica: horizontes editoriais para livros latentes - Thiago Figueiredo Landi Borges (2020)
This work is a contribution to the Publishing Studies, in regards to its activity in the theatrical scope. It seeks to establish an editorial thought specific to this artistic practice, that marks a singular way of working for the editor in the face of the theatrical phenomenon. To this end, it mobilizes concepts from the Semiology of Theatre, which has founded an understanding of the dramatic text as a scenic practice, therefore aimed at staging. In this sense, the text is part of a more complex phenomenon, which manifests its totality only in the scenic event. To this awareness is added another, that although text and scene have inseparable links in theatre, the scene has autonomous artistic value and little tradition of registration in the bookish world. These will be the guiding points that will lead us to speculate new publishing horizons for theatre, materialized in the concept of “latent book” – a reading project that links the text and the scene through a graphic work that appropriates the archives left by the scenic process. It is a practice that, although without a theoretical framework, has a historical trace since the early days of the press, which is briefly presented at the beginning of the work. The latent book also has contemporary examples, as shown by the four publications studied throughout the thesis, which, however, have not yet constituted a publishing tradition. The analysed works have in common the fact that they were conducted by emancipated editors who, therefore, take on the challenge of mediating the scene in the book They are: "As três irmãs, de Tchékhov, por Stanislávski", by Tieza Tissi; "Bodas de café", by Sonia Pascolati; "A navalha na carne", by Pedro Bandeira; and "Hysteria/Hygiene", by Grupo XIX de Teatro. The analysis demonstrates different ways of materializing a book such as this, thus contributing to consolidate the publishing horizons that this work intended to outline.